New species of Triplocania Roesler (Psocodea: ‘Psocoptera’: Ptiloneuridae) from Colombia and Peru - González-Obando, Ranulfo; Carrejo-Gironza, Nancy; Aldrete, Alfonso N. García (Zootaxa, 2021)
Based on a survey of species of the genus Triplocania (Psocodea: ‘Psocoptera’) in forests of natural areas of Colombia and Peru, 18 species (14 from Colombia and 4 from Peru) were found, 16 of which are new to science and two correspond to males of Colombian species originally described from females (T. matildae González et al., 2017, and T. sarriae González et al., 2017). The new species, here described and illustrated are: T. altamira n. sp., T. antioquensis n. sp., T. antisuyuensis n. sp., T. atratoensis n. sp., T. caguanensis n. sp., T. caquetensis n. sp., T. einsteini n. sp., T. fabridiazi n. sp., T. galileii n. sp., T. hawkingi n. sp., T. mancocapaci n. sp., T. molanoi n. sp., T. nerudai n. sp., T. roesleri n. sp., T. tahuantisuyuensis n. sp., and T. yupanquii n. sp. The number of species of Triplocania is now raised to 118. To date, the highest number of species are found in Colombia, Brazil and Peru, with 59, 34 and 9 species respectively. An updated identification key to the species of Triplocania (males) is included, as well as a classification of the species in the genus.